Analysis of physical and psychological factors in the context of Pencak Silat education for students - Muhammad Ridho Pambudi Pambudi; Syahrastani Syahrastani; Alnedral Alnedral; Tjung Hauw Sin (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This aims study investigates the influence of leg muscle power, flexibility, and self-confidence on the crescent kick speed of Pencak Silat athletes at the Laskar Silat Nusantara School in Kampar Regency. Employing a quantitative correlational design, the research involved 30 student-athletes selected through purposive sampling. Data were collected using standardized measurements: vertical jump for leg muscle power, sit-and-reach for flexibility, a psychological scale for self-confidence, and a stopwatch-based crescent kick speed test. Data analysis included descriptive statistics, Pearson product–moment correlation, and multiple regression. The findings show significant positive correlations between crescent kick speed and leg muscle power (r = 0.63), flexibility (r = 0.54), and self-confidence (r = 0.48). Multiple regression analysis further indicates that the three variables collectively contribute significantly to kick speed (p < 0.05), explaining 58% of its variance (R² = 0.58). Leg muscle power was identified as the strongest predictor. These results highlight the importance of integrating physical conditioning and psychological development to enhance technical performance. The study underscores the need for training programs that balance strength, flexibility, and mental readiness in martial arts education.